Comparison of Slow versus Rapid Feeding Regimen in Preterm Neonates in the reduction of hospital stay - Madiha Fayyaz , Shahzad Haider , Abdul Hameed Khan , Sajid Nazir , Alina Hassan , Sajjad Hussain , Madiha Fayyaz , Shahzad Haider , Abdul Hameed Khan , Sajid Nazir , Alina Hassan , Sajjad Hussain (Journal of Rawalpindi Medical College, 2020)
Introduction: In preterm babies delay in the achievement of full feeds causes prolonged hospital stay. This study will help in the nutritional management of preterm babies which will shorten the hospital stay and reduce the economic burdens on parents. Objective: To compare the mean duration of hospital stay of preterm neonates with two different feeding protocols(slow feeding regimen versus rapid feeding regimen). Materials and Methods: This study was conducted in the neonatal unit at Izzat Ali Shah Hospital from October 2019 to March 2020 through a randomized controlled trial. A total of 102 (51 in each group) were randomized to slow feeding (Group A) and Rapid feeding(Group B). Depending on the birth weight and gestational age, a certain amount of breast milk was initiated, with increments of 15-20 mL/kg/day in the slow feeding group & 25-30 ml/kg/day in the rapid feeding group. Feeding was stopped temporarily in case of any sign of feeding intolerance, suspected necrotizing enterocolitis, recurrent apnoeic episodes, and neonatal seizures. The total target feed was 180 ml/kg per day. Infants were continued in the study until discharged from the hospital. Results: Our study shows that the mean gestational agein Group A (Slow feeding) was 34 weeks with SD ± 2.68 while the mean gestational agein Group B (Rapid feeding) was 35 weeks with SD ± 1.98. In Group A (Slow feeding) 55% neonates were male while 45% neonates were female. Whereas in Group B (Rapid feeding) 57% neonates were male while 43% neonates were female. In Group A (Slow feeding) mean hospital stay was 22 days with SD ± 7.02. In Group B (Rapid feeding) mean hospital stay was 13 days with SD ± 3.72. Conclusion: Our study concludes that mean hospital stay in the rapid advancement of feeds was shorter as compared to the slow feeding of preterm neonates.